WHEN THE THYROID AND STOMACH COLLIDE: APS TYPE 3B BEHIND CARDIAC SYMPTOMS - Zulkifle, Aina Mardiah; Adam, Noor Lita; Karim, Nor Afidah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Autoimmune Polyglandular Syndromes (APS) are a group of disorders characterised by the simultaneous or sequential occurrence of multiple autoimmune-mediated diseases affecting endocrine glands. Pernicious anaemia is commonly part of this broader spectrum of autoimmune conditions. CASE We report the case of a 65-year-old male with a seven-year history of megaloblastic anaemia treated with cyanocobalamin, who presented with severe anaemia-induced non-ST-elevation myocardial infarction (NSTEMI) that manifested as chest pain, reduced exercise tolerance and profound fatigue. Initial investigations revealed pancytopenia, with a haemoglobin level of 5.0 g/dL, elevated mean corpuscular volume (142.2 fL), platelet count of 26 × 10⁹/L, white cell count of 0.9 × 10⁹/L, and significantly elevated troponin I levels (initially 2069 ng/L and rising to over 25,000 ng/L). Iron studies showed low serum iron (9.3 µmol/L), marginally elevated ferritin (325.3 ng/mL) and reduced total iron-binding capacity (40.84 µmol/L). Vitamin assays confirmed severe vitamin B12 deficiency (59 pmol/L) with elevated folate (49.2 nmol/L). Given the profound B12 deficiency, immunological testing revealed the presence of anti-parietal cell antibodies and elevated intrinsic factor IgG, which confirmed the diagnosis of pernicious anaemia. Given the clinical features suggestive of hypothyroidism, thyroid function testing was performed, revealing a free T4 of 4.3 pmol/L, TSH of 108.96 mIU/L and anti-thyroid peroxidase antibodies >600 IU/mL, consistent with Hashimoto’s thyroiditis. Levothyroxine and cyanocobalamin replacement therapy were initiated subsequently. These findings led to a diagnosis of APS type 3b, characterised by the coexistence of pernicious anaemia and Hashimoto’s thyroiditis. CONCLUSION Hashimoto’s thyroiditis (HT) and autoimmune gastritis (AIG) often coexist. Studies have shown that HT is present in 10–40% of patients with gastric disorders, and about 40% of those with AIG also have HT. This case emphasizes the need to screen for coexisting autoimmune conditions.